LITERASI DIGITAL SEBAGAI PENGUATAN PENDIDIKAN KARAKTER MENUJU ERA SOCIETY 5.0 - Bambang Yuniarto; Rivo Panji Yudha (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2021)
ABSTRACTThis article is the result of thinking about the importance of digital literacy for strengthening character education in the social 5.0 era. Civic education is an inseparable part and is reflected in the courses and learning forms of all levels of education and various fields. Within the framework of achieving the goals of national education, various functions and roles of civic education are designed and realized as manifestations. In the 5.0 era, citizenship is absolutely necessary. It requires people to master and balance the capabilities of artificial intelligence and social intelligence to solve various problems in the country. Society 5.0 provides an example of how to use data to mobilize and connect everything, including efforts to solve social problems. In short, students have the skills needed in the Social 5.0 era, including: leadership, digital literacy, communication, emotional intelligence, entrepreneurship, and global citizenship. The challenge of civic education is to provide the knowledge and skills of critical, constructive and creative thinking without departing from the emotional, social and spiritual wisdom of Pancasila and the 1945 Constitution.Â Keywords: Digital Literacy, Character, Society 5.0